D. B. Ramachary. Issue 16 (1st March 2018) - Unknown
Abstract: "I am constantly inspired by the people who have discovered green reactions and catalysts to make useful drugs in a simple manner." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201701617 . Abstract : "I am constantly inspired by the people who have discovered green reactions and catalysts to make useful drugs in a simple manner." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201701617 .